The Role of Gamification in Increasing Student Learning Motivation in Online Learning - M. Syahputra; Nandra Nandra; Aminah Aminah (Journal of Multidisciplinary Sustainability Asean, 2024)
Background. Online education has become an increasingly common learning method, but it often faces challenges in maintaining student motivation. Gamification, i.e. the application of game elements in non-gaming contexts, emerged as a potential strategy to increase engagement and motivation in online learning. Purpose. This study aims to explore the role of gamification in increasing students' learning motivation in online learning and to identify the most effective gamification elements in this context. Method. The method used is a quantitative approach with a survey design. Data was collected through a questionnaire filled out by 200 students from several high schools who participated in online learning with gamification elements. Statistical analysis was conducted to evaluate the relationship between gamification and learning motivation. Results. The results of the study showed that 70% of students had a high or very high level of motivation after applying gamification. Elements such as instant feedback obtained the highest scores in influencing motivation. Case studies show that 85% of students feel an increase in learning motivation in classrooms that implement gamification challenges. Conclusion. This study concludes that gamification can significantly increase students' learning motivation in online learning. The right implementation of gamification elements can create a more engaging and interactive learning experience, which is crucial in today's digital education.